2017
DOI: 10.1021/acs.jpcb.7b07517
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Design of the Triple-Decker Motif in Red Fluorescent Proteins

Abstract: We characterize computationally a red fluorescent protein (RFP) with the chromophore (Chro) sandwiched between two aromatic tyrosine rings in a triple-decker motif. According to the original proposal [ J. Phys. Chem. Lett. 2013 , 4 , 1743 ], such a tyrosine-chromophore-tyrosine π-stacked construct can be accommodated in the green fluorescent protein (GFP). A recent study [ ACS Chem. Biol. 2016 , 11 , 508 ] attempted to realize the triple-decker motif and obtained an RFP variant called mRojoA-VYGV with two tyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…17,18,23 Besides experimental efforts, molecular simulations also contributed to this field. 24,25 The π-stacking-induced spectral shifts in chromophores of the fluorescent proteins usually do not exceed 0.2 eV. This amount is comparable with an expected accuracy of modern quantum chemical methods in computing transition energies between the lowest electronic states.…”
Section: ■ Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…17,18,23 Besides experimental efforts, molecular simulations also contributed to this field. 24,25 The π-stacking-induced spectral shifts in chromophores of the fluorescent proteins usually do not exceed 0.2 eV. This amount is comparable with an expected accuracy of modern quantum chemical methods in computing transition energies between the lowest electronic states.…”
Section: ■ Introductionmentioning
confidence: 76%
“…Two quantum chemistry methods were utilized to obtain the electron density in the ground and excited states. First, the CASSCF approach is a method of choice when considering electronic excitations in organic chromophores. ,, Following our previous experience with the chromophores under study, , we rely on the distribution of 12 electrons over 12 active molecular orbitals and the density averaging over two lowest electronic states, S 0 and S 1 (sa2-CASSCF­(12/12)). The second option is the TDDFT approach; in this work, we employ the CAM-B3LYP, ωB97X-D3, and PBE0 functionals.…”
Section: Computational Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…The computational protocol PBE-D3/TZV2P-MOLOPT-GTH was used in QM, and the AMBER force field, in MM. The simulations showed that different starting conformations converged to similar structures with the triple-decker motif (see Figure 6 in ref ).…”
Section: Simulations Of Gfp-like Proteinsmentioning
confidence: 87%
“…On the basis of careful analysis of the protein structure of mRojoA, we suggested a series of mutations capable of fixing Tyr63 in a coplanar orientation with respect to the chromophore, along with the previously achieved π-stacking of the chromophore with Tyr197 (Figure ). Each replacement had a specific purpose.…”
Section: Simulations Of Gfp-like Proteinsmentioning
confidence: 99%